Safety procedures for total gastrectomy - Rinaldi, Bruno; Carriquiri, Luis; Praderi, Raúl C. (Cirugía del Uruguay, 1975)
The authors report a new procedúre to restore the digestive tract continuity after total gastrectomy. It consists of using an asymmetric jejunal loop (HivetWarren technique, modified). The loop must be previously disfunctionalyzed by a side-to-side anastomosis at its foot and section-suture of its afferent limb. The lower stump of this limb functions as a diverticular jejunostomy. It is used first as a decompressing device and later for feeding the patient. The upper stump is used to protect the esophago-jejunal anastomosis, by apposition of its serosa.